2023
DOI: 10.1038/s41559-023-02237-z
|View full text |Cite
|
Sign up to set email alerts
|

Recent co-evolution of two pandemic plant diseases in a multi-hybrid swarm

Mostafa Rahnama,
Bradford Condon,
João P. Ascari
et al.

Abstract: Most plant pathogens exhibit host specificity but when former barriers to infection break down, new diseases can rapidly emerge. For a number of fungal diseases, there is increasing evidence that hybridization plays a major role in driving host jumps. However, the relative contributions of existing variation versus new mutations in adapting to new host(s) is unclear. Here we reconstruct the evolutionary history of two recently emerged populations of the fungus Pyricularia oryzae that are responsible for two ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…The wheat blast population that has been expanding in South America since before its first discovery in 1985 is genetically complex. Indeed, a recent analysis showed that individual MoT genomes are composed of admixture contributions of chromosome segments derived from five different host-adapted populations of M. oryzae (Rahnama et al, 2023). Rahnama et al suggest the present-day population in South America is structured according to chromosomal haplotypes that were defined when various progeny inherited chromosome segments from different donors through sexual recombination.…”
Section: Discussionmentioning
confidence: 99%
“…The wheat blast population that has been expanding in South America since before its first discovery in 1985 is genetically complex. Indeed, a recent analysis showed that individual MoT genomes are composed of admixture contributions of chromosome segments derived from five different host-adapted populations of M. oryzae (Rahnama et al, 2023). Rahnama et al suggest the present-day population in South America is structured according to chromosomal haplotypes that were defined when various progeny inherited chromosome segments from different donors through sexual recombination.…”
Section: Discussionmentioning
confidence: 99%
“…Advancing genomic technologies are particularly tractable for the identification of emergent pathogens, especially in cases where culturing requires species-specific knowledge. Sequence-based methods can also be used to understand pathogen populations: to identify sources and important genomic regions, to inform management strategies to reduce transfers between reservoirs of diversity (e.g., [ 14 , 15 ]). Under investigated but equally important, we outline how genomic surveillance can identify haplotypic and structural variation which also facilitate introduction of novel diversity.…”
Section: How Do We Investigate Intraspecific Genomic Variation?mentioning
confidence: 99%
“…In many fungi, the somatic tissues are haploid and the power to detect the influence of recombination increases as assembly haplotypic contiguity increases, from targeted methods to pangenomics (see Table 1 ). At the species level, hybridisation recombines divergent genetic diversity and has been associated with host jumps [ 23 ] and increased pathogenicity, e.g., Dutch elm disease [ 15 ], and is visible as introgression [ 14 ].…”
Section: How Do We Investigate Intraspecific Genomic Variation?mentioning
confidence: 99%
See 1 more Smart Citation
“…Exchange of genetic information between host-specific isolates is thought to be rare, though there is clear evidence of such exchanges ( Gladieux, Condon, et al . 2018 ; Rahnama et al . 2023 ).…”
Section: Introductionmentioning
confidence: 99%